PENGEMBANGAN MEDIA BOOKLET TENTANG AKTIVITAS FISIK UNTUK PENCEGAHAN DIABETES MELITUS LEBIH LANJUT PADA PESERTA PROLANIS DI PUSKESMAS PAKUTANDANG - Abdillah, Muhammad Syukur (Politeknik Kesehatan Kemenkes Bandung, 2024)
Background : Diabetes mellitus affects 19,47 million people in Indonesia, with 2,148 cases in the Pakutandang Community Health Center working area. This high incidence is caused by lack of physical activity and lack of preventive information. Objective : Develop an easy to understand booklet about physical activity for the prevention of diabetes mellitus for prolanis participants at the Pakutandang Community Health Center. Methodology : The research uses a 4D model (Define,Design,Development,Dissemination) qualitative research was conducted with 5 prolanis participants through in-depth interviews. Quantitative research involved 1 material expert, 1 media expert, and 59 prolanis participants, using a media feasibility test questionnaire and feasibility percentage analysis. Result : indepth interviews highlighted the need for educational media in the form of booklets that are concise, clear and have meal menus for eldery, as well as attractive colors. The feasibility test showed a high percentage : 90% of material expert, 96% of media expert, and 91% of Prolanis participant. Booklet are distributed through Prolanis representatives. Conslusion : This Booklet is very suitable to be used as an educational medium for preventing diabetes mellitus in Prolanis participants at the Pakutandang Community Health Center.